TiO2 Co-doped with Zr and Ag shows highly efficient visible light photocatalytic behavior suitable for treatment of polluted water. Issue 69 (19th November 2020) - Aqeel, M.; Ikram, M.; Imran, M.; Ul-Hamid, A.; Qumar, U.; Shahbaz, A.; Ikram, M.; Saeed, A.
Abstract : The objective of this study is to analyze the effects of zirconium (Zr) and silver (Ag) doping on the photoactivity of titania (TiO2 ). Abstract : The objective of this study is to analyze the effects of zirconium (Zr) and silver (Ag) doping on the photoactivity of titania (TiO2 ). Zr–Ag (ZA) co-doped TiO2 products were fabricated via sol–gel technique and their properties (structural and chemical) were characterized. The weight ratio of TiO2 was fixed, while weight ratios of Zr and Ag were varied from 2 to 4, 6 and 8 wt% while synthesized samples were calcined at 400 °C for 3 h. The XRD results demonstrated that the incorporation of metal doping agents failed to alter the host material's lattice structure, however, its crystallite size was reduced from 13.54 to 5.05 nm with increasing Zr 4+ and Ag + concentrations. FTIR spectroscopy was used to examine various functional groups. In the attained spectra, an ample absorption peak between 500 and 1000 cm −1 was recorded, which was ascribed to Ti–O–Ti linkage vibration mode present within TiO2 . Surface morphology, microstructure, SAED patterns and elemental composition were examined with FE-SEM, HR-TEM and EDX, which served to confirm the ZA-doped TiO2 product. Band gap energy of the co-doped material was significantly reduced as indicated by a higher wavelength redshift in the spectra. The photoactivity and kinetics of photo-products were investigated by observing photo-decolorization of methylene blue (MB) under a radiation source. Photodecomposition of MB was dramatically enhanced when titania co-doped with Zr and Ag was employed compared to un-doped or mono-doped TiO2 . The ZA (8 wt%) co-doped TiO2 photocatalyst depicted the maximum MB removal efficiency (∼93%) within 90 min under a light source.